Molecular survey of haemoplasmas in shelter dogs and associations with Rhipicephalus sanguineus sensu lato - Aktas, M.; Ozubek, S. (Wiley, 2017)
This study aimed to assess the occurrence of canine haemoplasma infection in domestic dogs and its possible trans-stadial transmission by Rhipicephalus sanguineus sensu lato (Ixodida: Ixodidae) in shelter dogs in Diyarbakr Province in southeast Turkey. Blood samples (n=282) collected from domestic dogs were analysed by polymerase chain reaction (PCR) for the presence of canine haemoplasma. Fully engorged nymphs (n=204) were removed from dogs that were positive for canine haemoplasma by PCR and maintained in an incubator at 28 degrees C for moulting. Unfed ticks (n=2185) comprising 2100 nymphs and 85 adults collected from the grounds of the same shelter were also screened. Of 282 dogs, 108 [38.3%, 95% confidence interval (CI) 32.6-44.2] were PCR-positive for canine haemoplasmas. Mycoplasma haemocanis (Mhc) infection (26.2%, 95% CI 21.2-31.8) was observed in a significantly higher number of dogs than was CandidatusMycoplasma haematoparvum (CMhp) infection (6.7%, 95% CI 4.1-10.3). Co-infections were seen in 15 (5.3%, 95% CI 3.0-8.6) dogs. None of the tick specimens examined were found to be positive for haemoplasma. Partial sequences of the 16S ribosomal RNA (rRNA) gene shared 99-100% identity with the corresponding published sequences for Mhc and CMhp. The present results revealed no trans-stadial transmission of canine haemoplasma species by R.sanguineus s.l. in field conditions.
Keywords: Candidatus; Mycoplasma haematoparvum; Mycoplasma haemocanis; Rhipicephalus sanguineus s.l.; canine haemotropic mycoplasma; dog